Why are manual workers at high risk of upper limb disorders? The role of physical work factors in a random sample of workers in France (the Pays de la Loire study). Issue 11 (20th June 2006) - Melchior, M; Roquelaure, Y; Evanoff, B; Chastang, J-F; Ha, C; Imbernon, E; Goldberg, M; Leclerc, A
Abstract : Objective: To investigate the reasons for the excess risk of upper limb musculoskeletal disorders among manual workers compared with other workers in a random sample of 2656 French men and women (20–59 years old) participating in a study on the prevalence of work related upper limb disorders conducted by France's National Institute of Health Surveillance. Methods: Prevalence ratios (PR) of physician-diagnosed musculoskeletal disorders of the shoulder, elbow, wrist, and hand (any of six leading disorders, rotator cuff syndrome, carpal tunnel syndrome) in manual versus non-manual workers were calculated using Cox regression models with a constant time of follow up and robust variance. Results: 11.3% of men and 15.1% of women were diagnosed with an upper limb disorder. The risk was especially high in manual workers (PRs: 1.40 to 2.10). Physical work factors accounted for over 50% of occupational disparities overall, 62% (men) to 67% (women) for rotator cuff syndrome, and 96% (women) for carpal tunnel syndrome. The authors calculated that under lower levels of physical work exposures, up to 31% of cases among manual workers could have been prevented. Conclusions: In working men and women, upper limb musculoskeletal disorders are frequent. Physical work exposures, such as repetitive and forceful movements, are an important source of risk and in particular account for a large proportion of excess morbidity among manual workers.